TRATAMIENTO MEDICO DEL EMBARAZO ECTOPICO - Francisco Bueno N.; Jaime Sáez C.; Myriam Ocaranza B.; Carolina Conejeros R.; Italo Vaccarezza P.; Pamela Borquez V.; Emiliano Soto R. (Permanyer, 2002)
Se presenta el resultado de 21 casos de embarazo ectópico (EE) no complicados que fueron tratados con Metotrexato y manejo expectante, desde enero de 2000 a marzo de 2001. Objetivos: Conocer la incidencia del EE en nuestro servicio, evaluar la efectividad del tratamiento médico, y efectuar estudio de costos comparando tratamiento médico versus quirúrgico. Material y Métodos: Estudio prospectivo de 21 casos de EE no complicados hospitalizados en la Unidad de alto riesgo, trece casos manejados con Metotrexato parenteral y ocho casos con manejo expectante. Resultados: En 3 casos se requirió resolución quirúrgica secundaria, determinando una tasa de éxito de tratamiento médico de 85,7%. No hubo correlación entre el nivel inicial de ß-HCG con el tamaño de masa anexial, tiempo de negativización de ß-HCG, necesidad de segunda dosis de MTX ni aparición de complicaciones del EE durante el tratamiento. Costo total, un 22,7% inferior para el tratamiento médico con respecto a cirugía. Conclusión: Las dos alternativas de tratamiento médico analizadas, son válidas en pacientes con EE no complicado. Twenty one non complicated ectopic pregnancy are presented; some of which were treated with methotrexate and the rest with conservative unnassisted medication from January 2000 to March 2001. Objetive: To measure the incidence of ectopic pregnancy in our department; to evaluate the effectiveness of the medical treatment prescribed and to study medical versus surgical treatment costs. Material and Methods: Prospective study of 21 cases of non complicated ectopic pregnanty, thirteen cases managed with parenteral methotrexate and eight cases with expectant management. Results: In three cases surgical treatment was required, determining success of medical treatment in 85.7%. There was not correlation between the initial level of serum HCG, with the size of the adnexal mass, the time of declining of HCG, necessity of secondary dose of methtorexate nor the apparition of complication during treatment. Total cost of medical treatment was 22.7% lower than surgical treatment. Conclusion: The two alternatives of medical treatment, that is, medical with methotrexate and expentat management are valid in patient with non complicated ectopic pregnancy.